ANALISIS KEKUATAN BEARING PADA MESIN GRANULATOR TERHADAP PEMBEBANAN STATIS MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS (FEA) - Bayu Pradana, Muhamad Rizki; Anam, Chairul; Yuniwati, Ika; Umar, Mega Lazuardi; Sari, Eli Novita (Universitas Sriwijaya, 2024)
The main objective of this study is to develop a highly accurate, high-fidelity model of bearing geometry, which reflects the actual geometry of the bearing to ensure the validity of the analysis. The model will carefully take into account various geometric parameters, such as bearing dimensions and tolerances, and detect potential errors in the model. Simulations are carried out by applying realistic static loads and boundary conditions, close to actual operating conditions, to obtain relevant and practical results. In addition, calculations and analysis of stress distribution throughout the bearing are also carried out, with the aim of identifying stress distribution patterns and determining areas with the highest stress. This analysis is crucial for detecting possible failures and ensuring optimal bearing design. Deformation in various parts of the bearing is measured to understand changes in shape and stiffness of the structure under load. This measurement aims to find the area with the highest deformation and evaluate the bearing response to the applied load. Finally, an evaluation of bearing safety factors is carried out to ensure sufficient safety margins in accordance with industry standards, with the hope of ensuring the reliability and long-term service life of the bearing as well as improving the performance and efficiency of the mechanical systems that use it.